Determinação da constante de afinidade e cinética da interação lectina ArtinM-célula leucêmica (NB4) por meio de técnicas piezoelétrica e eletroquímica - Martins, Denise Cristina [UNESP] (2013)
ArtinM, a D-mannose-binding lectin from Artocarpus heterophyllus (jackfruit), interacts with N-glycans on cell surface receptors triggering cell migration, degranulation, and cytokine release. Because malignant transformation is often associated with altered expression of cell surface glycans, this work evaluated the interaction of ArtinM with human myelocytic leukemia cells, such as acute promyelocytic leukemia, NB4, by piezoelectric techniques of the Quartz Crystal Microbalance (QCM) and by electrochemical techniques of Electrochemical Impedance Spectroscopy (EIS). It was developed, for both techniques, a surface recognition capable of performing the biological interaction between lectin-cell and transducte them in electric signal. The surface was formed by immobilization of ArtinM in Au metal surfaces by over a self-organized monolayer constructed by a mixture of two alkanothiols, 11-mercaptoundecanoic acid (11-MUA) as an anchor, and 6-mercaptoethanol (6- MetOH) as a spacer. Concentrations of NB4 cells, previously fixed with paraformaldeide, were left in contact with the immobilized lectin on electrode. After the interaction measurements evaluated by QCM and EIS, and applying the model of Langmuir isotherm, it was possible to obtained both kinetic and affinity constants. Using QCM, beyond the apparent affinity constant, was possible to extract kinetic parameters Ka (association kinetic constant) = (1.8 ± 1.1) 10-7 cel mL-1, kon (association constant) = (3.6 ± 1.0) x10- 10 mL cel- 1 s- 1 and koff (dissociation constant) = (20.3 ± 6.6) x10- 4 s- 1 . The value of the apparent affinity constant (K') was (4.4 ± 0.1) x10- 7 cel mL- 1 by QCM and (9.9 ± 0.2) x10- 5 mL cel- 1 by EIS, the difference between the values comparing both techniques may be related to different factors such as the use of successive addition of NB4 in EIS comparing the in unitary addition in QCM analysis, variation in surface engineering and distinct saturation range.